1988
DOI: 10.1346/ccmn.1988.0360504
|View full text |Cite
|
Sign up to set email alerts
|

Modified Clays for the Adsorption of Environmental Toxicants: Binding of Chlorophenols to Pillared, Delaminated, and Hydroxy-Interlayered Smectites

Abstract: Abstract--Due to their unique polarity, pore-size distribution, and high surface areas, pillared and delaminated clays are potentially useful materials for the adsorption of environmenlal toxicants. To determine their properties for adsorption of chlorinated phenols, alumina-pillared montmorillonite (APM), chromia-pillared montmorillonite (CPM), and alumina-delaminated Laponite (ADL) were reacted with aqueous pentachlorophenol (PCP) solutions in batch equilibrium experiments. An hydroxy-A1 Laponite (HAL) in wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
1
2

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(46 citation statements)
references
References 30 publications
2
40
1
2
Order By: Relevance
“…At pH 10.5, neither of these two classes of sites is preferred by the phenolate anion. It is interesting to note that in the case of the adsorption of PCP on alumina pillared montmorillonire at acidic pH (Zielke and Pinnavaia, 1988), the adsorbed quantities were much smaller than those obtained for our surfactant-modified pillared clay. Clearly, chemical modification by eoadsorption of nonionic surfactant increases the binding energy of the surfaces, thus dramatically improving PCP adsorption.…”
Section: Influence Of Ph On Pentachlorophenol Adsorptioncontrasting
confidence: 59%
See 2 more Smart Citations
“…At pH 10.5, neither of these two classes of sites is preferred by the phenolate anion. It is interesting to note that in the case of the adsorption of PCP on alumina pillared montmorillonire at acidic pH (Zielke and Pinnavaia, 1988), the adsorbed quantities were much smaller than those obtained for our surfactant-modified pillared clay. Clearly, chemical modification by eoadsorption of nonionic surfactant increases the binding energy of the surfaces, thus dramatically improving PCP adsorption.…”
Section: Influence Of Ph On Pentachlorophenol Adsorptioncontrasting
confidence: 59%
“…In order to obtain a better understanding of the PCP adsorption mechanisms, it was necessary to replot the isotherms relative to the degree of undersaturation, as shown in Figure 5B. In a paper dealing with the adsorption of chlorinated phenols on pillared and delaminated clays, Zielke and Pinnavaia (1988) showed that pentachlorophenol adsorption was very much influenced by the equilibrium pH, with almost no measurable uptake for equilibrium pH > 7. In contrast, pentachlorophenol adsorption on organo-clays is also pH independent (Boyd et al, 1988).…”
Section: Influence Of Ph On Pentachlorophenol Adsorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…3-CP (pK1 = 9.02) was sorbed as a neutral molecule. According to Zielke and Pinnavaia (1989), neutral chlorophenol molecules are preferred by Al-pillared montmorillonite over the phenolate forms.…”
Section: Sorption Of 3-cpmentioning
confidence: 99%
“…In this context, the possibility of sorbents in the purification of contaminated water, e.g., for in situ leachate treatment in waste-disposal containment systems, should be investigated. For some compounds, such as chlorophenols, it was shown that hydroxy-intercalated and pillared bentonites may be better sorbents than untreated bentonites owing to their high surface acidity and surface area (Zielke and Pinnavaia, 1989).…”
Section: Introductionmentioning
confidence: 99%